Further records of jewel beetles (Coleoptera: Buprestidae) from Oman - Al-Jahdhami, Ali A. (2021)
Buprestidae beetles are herbivorous and often strictly associated with their host plant. The knowledge of Buprestidae from Oman is still incipient. Less than 25 species of Buprestidae are reported from Oman so far and this indicates the large blank in our knowledge in this family when compared to recorded species from other neighboring countries in the Arabian Peninsula. In this paper, seven species from four genera and three subfamilies are being new records for Oman. The number of new records in Agrilinae subfamily are four species (Agrilus (Diplolophotus) desertus (Klug, 1829), Agrilus (Micragrilus) lituratus (Klug, 1829), Agrilus purpuratus (Klug, 1829), Agrilus (Agrilomorpha) venosus Gory & Laporte, 1837, two from Buprestinae (Chrysobothris (Chrysobothris) parvipunctata Obenberger, 1914, Melanophila cuspidata (Klug, 1829)) and one from Chrysochroinae (Paratassa arabica Bílý & Volkovitsh, 1996).